Hidden Criticism? the Methodology and Plausibility of the Search for a Counter-Imperial Subtext in Paul - Heilig, Christoph 1990- (Tübingen Mohr Siebeck, 2015)
1.1 Introduction1.2 N.T. Wright: The Empire as Oppressor of God's People; 1.3 John M.G. Barclay: The Empire as a Consciously Ignored Peripheral Phenomenon; 1.4 Evaluation: What is the Real Plight?; 2. From Attitude to Expression: Modifications of the Echo-Hypothesis; 2.1 Paul's Personality as Obstacle for the Echo-Hypothesis; 2.2 Two Modification of the Classical Echo-Hypothesis; Chapter 6: Explanatory Context; 1. Introducing Explanatory Potential; 2. Establishing Parallels between Paul and the Empire; 2.1 Termini Technici; 2.2 Chance?; 2.3 True and False Alternatives.
2.4 Explanatory Potential and Background Plausibility of a Hypothesis2.5 Background Knowledge; 2.6 Comparing Hypotheses ; 2.7 Conclusions; 3. "Echoes" of the Empire; 3.1 Hays's Criteria for Identifying Scriptural "Echoes"; 3.2 Application to Imperial Ideology; 3.3 Methodological Evaluation; 4. Excursus: Inference to the Best Explanation; Chapter 3: Discourse Context; 1. Introduction; 2. James C. Scott's Categories; 2.1 The Public Transcript; 2.2 The Hidden Transcript; 2.3 The Hidden Transcript and the Public Sphere; 3. Application to the Pauline Letter.
3. From Intertextuality to Criticism: Neutral Parallel or Antithesis?3.1 Non-Roman "Echoes" with and without Counter-Imperial "Resonance"; 3.2 Imperial References with and without Critical Intention: Neutral Parallel or Antithesis?; Chapter 7: Conclusions; 1. Summary; 2. Outlook; Bibliography; 1. Sources; 2. Tools; 3. Secondary Literature; Index of Ancient Sources; 1 Old Testament; 2 Apocrypha; 3 Dead Sea Scroll; 4 New Testament; 5 Josephus; 6 Philo; 7 Early Church; 8 Greek and Roman Authors; 9 Non-Literary Sources; Index of Modern Authors; Index of Subjects.
3.1 The Pauline Letters as Hidden Transcript in Veiled Form?3.2 Pauline Letters as Hidden Transcript in Pure Form?; 3.3 Conclusions; Chapter 4: Roman Context; 1. The Public Transcript; 1.1 Criticism within the Framework of the Public Transcript?; 1.2 Different Objects of Criticism; 1.3 Conclusions: Modification of the Object of Criticism; 2. Roman Ideology in the Environment of Paul; 2.1 Introduction; 2.2 Imperial Cults as an Expression of Imperial Ideology; 2.3 Other Expressions of Imperial Ideology; 2.4 Conclusions ; Chapter 5: Pauline Context; 1. Counter-Imperial Attitude?
Cover; Preface; Table of Contents; Abbreviations; Chapter 1: Analogy; 1. Introduction; 1.1 Point of Departure; 1.2 Goodenough's Proposal: Veiled Criticism of the Roman Empire in Somn. 2; 1.3 Philo's Political Theory; 2. Analysis of Somn. 2; 2.1 Preliminary Remarks on Procedure; 2.2 Somn. 2 and the Allegory of the Soul; 2.3 Political Allegory in Somn. 2?; 3. Conclusions; 3.1 Summary; 3.2 Outlook; Chapter 2: Approach; 1. Counter-Imperial "Echoes" in the Subtext; 2. Evaluating Hypotheses; 2.1 On the Nature of Criteria; 2.2 The Structure of Historical Inferences; 2.3 Bayes's Theorem.
Paul has been regarded as being uncritical of the Roman Empire for a long time, not least because of his apparent call to obey the state in Rom 13:1-7. However, recent scholarship has questioned this assumption by pointing to ""hidden criticism"" in the letters of the apostle. But how can we decide, in a methodologically sound way, whether such a counter-imperial message lies beneath the surface of the text? On the basis of insights from the philosophy of science, Christoph Heilig suggests several analytical steps for examining this paradigm. He concludes that the hypothesis that we can identi
Keywords: Bible -- Criticism, interpretation, etc; Religion and state -- Biblical teaching; Bible; Christianity; RELIGION / Christian Theology / History; Religion and state ; Biblical teaching; Criticism, interpretation, etc; Electronic books